Peran Inovasi Digital Melalui Program KRENOVA sebagai Strategi Ketahanan Sosial Urban di Kota Surakarta - Oktovia Putri Ramadhani; Nugraheni Dwi Hastuti; Yuyun Sunesti (Jurnal Bengawan Solo Pusat Kajian Penelitian dan Pengembangan Daerah Kota Surakarta, 2025)
The economic crisis affecting urban communities has created complex social challenges, such as rising unemployment, economic inequality, and declining community solidarity. This study aims to examine the role of digital innovation integrated into the Community Creativity and Innovation Program (KRENOVA) as a strategy for strengthening social resilience in urban areas, specifically in Surakarta City. Using a literature study method and a descriptive-analytical approach, this research provides a comprehensive understanding of how digital innovation can enhance social connectivity, citizen participation, and community-based economic empowerment. The findings show that digital initiatives—such as online public service platforms, MSME digitalization, and community communication channels—help sustain social networks during crises. KRENOVA, facilitated by the Regional Research and Innovation Agency (BRIDA), also promotes the development of adaptive solutions rooted in local wisdom. The synergy between technology, community participation, and public policy effectively shapes a resilient, inclusive, and sustainable social system. This study emphasizes the importance of collaborative approaches in building urban social resilience that responds to the economic and social dynamics of urban life.